Comparative Analysis Of Non-Performing Financing At PT. Bank Syariah Indonesia, TBK (BSI) Before And After The Merger - Alim Bahri; Rulyanti Susi Wardhani (CV Putra Publisher, 2023)
Three government-owned Islamic banks were merged, namely PT. Bank BRI Syariah, PT. Bank BNI Syariah, and PT. Bank Mandiri Syariah became PT. Bank Syariah Indonesia (BSI) is an effort to improve the financial performance of Islamic banks so that they can be more competitive. This study aims to test and analyze differences in non-performing financing before the merger (2019 quarter II – 2020 quarter IV) and after (2021 quarter I - 2022 quarter III). The sample in this study is the quarterly financial reports of Bank BSI. The analytical method is a descriptive comparative method and uses a paired sample t-test analysis technique. The study results show significant differences in non-performing financing before and after the merger, which indicates that the union influences the risk of problem financing.